2020
DOI: 10.1159/000513425
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury and Renal Replacement Therapy in Critically Ill COVID-19 Patients: Risk Factors and Outcomes: A Single-Center Experience in Brazil

Abstract: <b><i>Background:</i></b> Critically ill patients with COVID-19 may develop multiple organ dysfunction syndrome, including acute kidney injury (AKI). We report the incidence, risk factors, associations, and outcomes of AKI and renal replacement therapy (RRT) in critically ill COVID-19 patients. <b><i>Methods:</i></b> We performed a retrospective cohort study of adult patients with COVID-19 diagnosis admitted to the intensive care unit (ICU) between March 2020 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 42 publications
5
40
1
9
Order By: Relevance
“…69.3% and 65.3% of AKI patients required mechanical ventilation and vasopressors, respectively. In addition, the 60day AKI mortality and 60-day AKI-RRT mortality rates were 23.8% and 35.3%, respectively [3]. Possible reasons for this much lower mortality than has been found in other studies could be the lower prevalence of KDIGO stage 3, the short time interval between COVID-19 symptom onset and ICU admission (only 1 day), and the study setting (private medical service with better resources).…”
Section: Patient Characteristicsmentioning
confidence: 66%
See 1 more Smart Citation
“…69.3% and 65.3% of AKI patients required mechanical ventilation and vasopressors, respectively. In addition, the 60day AKI mortality and 60-day AKI-RRT mortality rates were 23.8% and 35.3%, respectively [3]. Possible reasons for this much lower mortality than has been found in other studies could be the lower prevalence of KDIGO stage 3, the short time interval between COVID-19 symptom onset and ICU admission (only 1 day), and the study setting (private medical service with better resources).…”
Section: Patient Characteristicsmentioning
confidence: 66%
“…Nephrologists have witnessed that, as in other infectious diseases, acute kidney injury is a frequent complication of SARS-CoV-2, especially in its most severe forms. Current data demonstrate a prevalence of up to 56.9% of acute kidney injury among hospitalized patients with SARS-CoV-2 and mortality that varies widely (23.8-97.2%) depending on the characteristics of the sample [3,4]. It has been suggested that COVID-19 associated AKI has a worse prognosis in comparison to other AKI etiologies [5].…”
Section: Introductionmentioning
confidence: 97%
“…In an English multicentric series (32) of 1,032 inpatients, of which 165 were in the ICU, the incidence of AKI in critical patients was 44.2% with a higher mortality in patients with AKI compared with non-AKI patients (52.1 vs. 22.8, p < 0.001) with similar results observed in French patients (33). In a Brazilian single-center study (34) with 201 ICU patients, 101 (50.2%) developed AKI and 32 (17%) required dialysis. The overall mortality was 14.4%, being higher in the AKI group of patients.…”
Section: Discussionmentioning
confidence: 62%
“…Due to the preserved diuresis, such patients did not develop uremia, hypervolemia, or other hydroelectrolytic disorders that required dialysis treatment. Regarding risk factors for mortality in COVID-19 patients, another case series (29)(30)(31)34) found a correlation between obesity and mortality. This finding was not evidenced in our cohort; however, only 30.5% of the patients had an obesity diagnosis with most of them having a BMI in the range from 24.7 to 30.4 kg/m 2 (p25; p75), differently from those from other series in which the obesity percentage and the BMI values were both higher.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation